ANALYSIS OF INTERNAL CONTROL AND ACCOUNTING INFORMATION SYSTEMS ON DECISIONS TO GRANTING CREDIT AT PT BPR ANUGERAH BINTANG SEJAHTERA IN PEKANBARU - Asepma Hygie; Deviana Sofyan; Refni Sukmadewi; Asraf Asraf (Strategic Management Business Journal, 2023)
This study aims to determine the analysis of accounting information systems and internal controls on credit purchasing decisions at PT BPR Anugerah Bintang Sejahtera in Pekanbaru. The population in this study is the number of employees at PT BPR Anugerah Bintang Sejahtera Pekanbaru as many as 16 people consisting of 8 female employees and 8 male employees. The sample in this study were 3 people, including the Director, Credit Analyst, and Credit Admin. Sugiyono, (2014: 224) argues that data collection techniques are the most strategic steps in research, because the main objective of research is to obtain data. The data collection techniques used in this study were observations and interviews. The data analysis technique used in this study is a qualitative descriptive analysis technique using interviews and documentation. The accounting information system for lending decisions at PT BPR Anugerah Bintang Sejahtera is generally good, this can be seen from the fulfillment of the elements of the credit granting system in accordance with the underlying theory, except for serial numbers that are not printed. The application of the credit granting internal control system implemented by PT BPR Anugerah Bintang Sejahtera is said to be still not good when viewed from the credit granting procedures.